Potential Uses of Spent Mushroom Substrate Containing Palm Pressed Fiber as Organic Fertilizer: Study on Chemical Analysis and Lignocellulose Biodegradation - Hidayat, Mohamad Rusdi (Waste Technology, 2017)
One of the applications of palm pressed fiber (PPF), which generated from palm oil industry, is as an alternative medium for mushroom production. Increased usage of PPF by mushroom farms ultimately would raise the mushroom substrate waste or commonly called as spent mushroom substrate (SMS) containing PPF. Although beneficial effects of SMS on the crops growth have been investigated in recent years, the SMS characterization studies are still limited. SMS characterization is required since its properties are determined by many factors, and its characteristics could affect its effectiveness as organic fertilizer. Therefore, the aim of this study was to characterize fresh PPF based-SMS from Pleurotus ostreatus cultivation. All parameters tested were performed based on the regulation of the Indonesian Ministry of Agriculture No. 70-2011 about organic fertilizer. Moreover, lignocellulose biodegradation analysis of the SMS before and after mushroom cultivation also conducted. Results showed that fresh SMS composed of 50% and 100% of PPF meet the quality standards as organic fertilizer. This finding suggests that fresh PPF-based SMS could be applied directly as organic fertilizer without further composting process.